2009
DOI: 10.1093/cercor/bhp091
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar Inputs to Intraparietal Cortex Areas LIP and MIP: Functional Frameworks for Adaptive Control of Eye Movements, Reaching, and Arm/Eye/Head Movement Coordination

Abstract: Using retrograde transneuronal transfer of rabies virus in combination with a conventional tracer (cholera toxin B), we studied simultaneously direct (thalamocortical) and polysynaptic inputs to the ventral lateral intraparietal area (LIPv) and the medial intraparietal area (MIP) in nonhuman primates. We found that these areas receive major disynaptic inputs from specific portions of the cerebellar nuclei, the ventral dentate (D), and ventrolateral interpositus posterior (IP). Area LIPv receives inputs from oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
217
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(230 citation statements)
references
References 110 publications
(196 reference statements)
12
217
0
1
Order By: Relevance
“…S1 . We add that previous studies employing transneuronal retrograde tracing also showed cerebellar projections to areas AIP and 7b 24 and to LIP and VIP 25 .…”
Section: Sdusupporting
confidence: 71%
“…S1 . We add that previous studies employing transneuronal retrograde tracing also showed cerebellar projections to areas AIP and 7b 24 and to LIP and VIP 25 .…”
Section: Sdusupporting
confidence: 71%
“…1 and Table S1). RV is transported transneuronally in the retrograde direction in a time-dependent fashion in nonhuman primates (4)(5)(6)(7)(8). We set the survival time at 42 h to allow two stages of transport: retrograde transport of RV to first-order neurons that project to the injection site and then, retrograde transneuronal transport of the virus to second-order neurons that make synaptic connections with the first-order neurons.…”
Section: Resultsmentioning
confidence: 99%
“…When all injections were completed, the cerebellum was covered with artificial dura and the incision was closed in anatomical layers. The monkeys were placed in an isolation chamber and administered an analgesic (buprenorphine; 0.01 mg/kg) and dexamethasone (0.25 mg/kg) every 12 h. Prior studies have demonstrated that RV is transported exclusively in the retrograde direction in a time-dependent fashion (4)(5)(6)(7)(8). The available evidence suggests that the spread of RV is exclusively transsynaptic and that the virus is neither taken up by fibers of passage nor transported between neurons and glia (5).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, saccade adaptation was reduced in patients with lesions in the cerebral thalamus (Gaymard et al, 2001). Cerebellar projections to the parietal cortex via cerebellothalamocortical pathways have been shown to be functionally relevant for the adaptive control of eye movements as well as for adaptation of visual localization (Prevosto et al, 2010). Our results leave open the possibility that the adaptation and mislocalization effects are functionally spatiotopic.…”
Section: Discussionmentioning
confidence: 52%